Eco-Packaging : The Role of Attitude & Brand Image in Green Purchases - Manuaba, Ida Ayu Mas Pramesthi Dharma Dewi; Muna, Nilna (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study aims to analyze the effect of green packaging on green purchase intention by considering the role of attitude (green attitude) as an intervening variable and brand image as a moderating variable. The background of this study is based on the increasing problem of plastic pollution and the need for sustainable solutions. The method used is a quantitative approach with data collection through questionnaires distributed to 190 respondents in Denpasar City. The results of the analysis using Structural Equation Modeling (SEM) show that green packaging has a significant effect on attitudes and green purchase intentions. In addition, attitude is also proven to mediate the relationship between green packaging and purchase intention. However, brand image does not show a significant moderating effect. The conclusion of this study confirms the importance of green packaging in increasing consumers' positive attitudes and their purchase intentions towards green products, while brand image needs to be further considered for the development of effective marketing strategies.